The Effect of Social Support on Stress Levels of Health Workers During The COVID-19 Pandemic: A Literature Review - Riris Diana Rachmayanti; Kamila Fihir Bawazier; Takako Yasutome; Rachmah Indawati; Aninditya Ardhana Riswari; Ismayani Ismayani; Andrei Ramani; Anysiah Elly Yulianti; Jayanti Dian Eka Sari (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2023)
Background: The COVID-19 pandemic has caused various changes in the social dynamics of life. Almost all age groups in various countries are forced to adopt new habits that have the potential to interfere with mental health. Providing social support can be useful for reducing the stress level of health workers. Proper social support can overcome stress problems. The purpose of this study was to analyze the effect of social support on the stress level of health workers during the COVID-19 pandemic.Method: This is a literature review using population, intervention, comparison, results, research design, and keywords used according to the research topic. Keyword use Mesh term strategy with the term